2011
DOI: 10.1002/jmri.22641
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tissue phase mapping: Analysis of age‐related and pathologically altered left ventricular radial and long‐axis dyssynchrony

Abstract: Purpose: To employ magnetic resonance tissue phase mapping (TPM) for the assessment of age-related left ventricular (LV) synchrony of radial and long-axis motion in healthy volunteers and in hypertensive heart disease, dilated cardiomyopathy (DCM), and left bundle branch block (LBBB).Materials and Methods: TPM (spatial/temporal resolution ¼ 1.3 Â 2.6 mm 2 /13.8 msec) was employed to measure radial and long-axis myocardial velocities in 58 healthy volunteers of three age groups and 37 patients (hypertensive, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(27 reference statements)
3
11
1
Order By: Relevance
“…Previous studies of LV myocardial function and dyssynchrony in aging people have not observed individuals older than 89 years of age [8,9,11-13,17,18,28]. In the present study, our participants were aged up to 94 years.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies of LV myocardial function and dyssynchrony in aging people have not observed individuals older than 89 years of age [8,9,11-13,17,18,28]. In the present study, our participants were aged up to 94 years.…”
Section: Discussionmentioning
confidence: 86%
“…Only two MRI studies have observed increasing myocardial dyssynchrony in healthy aging people [17,18], while no studies have previously examined age-related changes in EAT in healthy males. We found the combination of EAT, longitudinal, and circumferential LV-dyssynchrony at the base explained more than one-third of the variability in longitudinal strain and LV twist, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters derived from velocity-time curves were introduced for tissue phase mapped imaging and include the standard deviation of the time to the systolic and diastolic peak [17] and the asynchrony correlation coefficient [18]. Reduced systolic and diastolic velocities have been reported in patients selected for cardiac resynchronization patients (CRT) and patients suffering from myocardial infarction [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation of the time to systolic and diastolic peak (σ TTP ) has been assessed and increased σ TTP values have been found to be significantly increased in DCM patients [17]. …”
Section: Introductionmentioning
confidence: 99%